Nutrientes digestíveis totais e energia digestível do feno de soja perene (Glycine Javanica L) em diferentes idades - Prado Rennó, Fransisco; da Silva, Dirceu Jorge; Campos, Joaquim (Revista Ceres, 2025)
This work was conducted at the Federal University of Viçosa to study the total digestible nutrients, digestible energy and the caloric value of the total digestible nutrients of perennial soybean hay (Glycine javanica L.) at 60, 108 and 157 days of age.